Integration of Market Development Strategy with Digital Marketing and Integrated Marketing Communication on SMES Kribo - Dessy Elliyana; Dwi Kurniawan; Feny Tialonawarmi (Universitas Batanghari Jambi, 2026)
The economic growth of Micro, small and medium is currently one of the business sectors that contribute to the regional economy. KRIBO has the potential to develop its business through digital marketing and integrated marketing communication through the right communication media, because some sales transactions are done digitally and online. The level of readiness to use digital marketing in the application used has an effect on the message that will be received or delivered to consumers. The IMC concept integrating businesses and integrates all communication channels in conveying the message of a product consistently and clearly. Furthermore, digital marketing significantly strengthens IMC by facilitating consistent and interactive communication across multiple digital platforms. Both digital marketing and IMC have significant positive effects on marketing performance, measured by market expansion, customer acquisition, brand awareness, and sales growth. The results demonstrate that integrating these strategic elements enables SMEs to respond more effectively to changing customer preferences, improve competitive advantage, and support long-term business sustainability. This study contributes to the marketing and SME literature by proposing an integrated framework that combines market development strategy, digital marketing, and IMC. The findings also provide practical implications for SME managers and policymakers seeking to strengthen SME competitiveness through digital transformation and coordinated marketing communication strategies.